GAMBARAN PRAKTIK KEPATUHAN MINUM OBAT DALAM PENGOBATAN MASSAL FILARIASIS LIMFATIK PUTARAN KEDUA DI WILAYAH KERJA PUSKESMAS LEYANGAN KABUPATEN SEMARANG - Melina Setyawati; Praba Ginandjar; Lintang Dian Saraswati; Martini Martini (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2020)
Drug coverage of taking mass drug administration in the region of Leyangan Health Center decreased in the first round to the second round that is drug coverage of the total population from 77.4% to 51.12%, and drug coverage of the target population was decreased from 99.9% to 69.61%. Decreasing the drug coverage below the target of drug coverage of the total population (≥ 65%) and target population (≥ 85%) is related to compliance. This is a descriptive study which describes the compliance of taking the mass drug in the second round of MDA in the region of Leyangan Public Health Center, Semarang Regency. The population of this study is 28,282 population targeted for MDA and the sample of 210 target populations who received the mass drug. The sampling technique used two-stage cluster sampling. The analysis used univariate and bivariate descriptive. The results of this study demonstrate that the proportion of compliance to MDA is 58,1%. The proportion of compliance to MDA are higher at age group ≥ 61 years (75.0%), women (61.7%), graduated from the academy or college (62.9%), occupation (61.3%), married (60.9%), good filariasis knowledge (62.7%), good MDA knowledge (64.8%), positive susceptibility perception (68.1%), positive severity perception (64.7%), positive benefits perception (72.6%), negative barriers perception (89.5%), receive cadre support (79.2%), receive social support (65.6%) and have experience of drug side effects (87.2%).